Bacterial species with different nanocolony morphologies have distinct flow-dependent colonization behaviors - Kelsey M. Hallinen; Steven P. Bodine; Howard A. Stone; Tom W. Muir; Ned S. Wingreen; Zemer Gitai (Proceedings of the National Academy of Sciences, 2025)
Fluid flows are dominant features of many bacterial environments, and flow can often impact bacterial behaviors in unexpected ways. For example, the most common type of cardiovascular infection is heart valve colonization by gram-positive bacteria like Staphylococcus aureus and Enterococcus faecalis (endocarditis). This behavior is counterintuitive because heart valves experience high shear rates that would naively be expected to reduce colonization. To determine whether these bacteria preferentially colonize higher shear rate environments, we developed a microfluidic system to quantify the effect of flow conditions on the colonization of S. aureus and E. faecalis . We find that the preferential colonization in high flow of both species is not specific to heart valves and can be found in simple configurations lacking any host factors. This behavior enables bacteria that are outcompeted in low flow to dominate in high flow. Surprisingly, experimental and computational studies reveal that the two species achieve this behavior via distinct mechanisms. S. aureus grows in cell clusters and produces a dispersal signal whose transport is affected by shear rate. Meanwhile, E. faecalis grows in linear chains whose mechanical properties result in less dispersal in the presence of higher shear force. In addition to establishing two divergent mechanisms by which these bacteria each preferentially colonize high-flow environments, our findings highlight the importance of understanding bacterial behaviors at the level of collective interactions among cells. These results suggest that distinct multicellular nanocolony morphologies have previously unappreciated costs and benefits in different environments, like those introduced by fluid flow.